Pengaruh Penerapan Gaya Mengajar Latihan Terhadap Peningkatan Ketrampilan Forehand Overhead Clear Dalam Permainan Bulutangkis Pada Peserta Didik SMA Negeri 2 Tondano - Pinangkaan, Edita A.M.; Ramli, Musdalifah; Sahruni, Ade Yuni (Jurnal Porkes, 2025)
This study aims to determine the effect of applying the training teaching style on forehand overhead clear skills in badminton. This study employs an experimental method with a randomized control group pretest and posttest design. The study population consists of all 40 students in the 11th grade at SMA Negeri 2 Tondano, with a sample size of 20 students. Data collection techniques utilize a skill test. The research instrument used is a standardized forehand overhead clear skill test with a scoring system of 1–4 points per stroke. Data analysis results From the hypothesis testing calculations, the calculated t-value was 6.01. Based on the t-distribution table at α 0.05 with degrees of freedom n1 + n2 - 2 = 10 + 10 – 2 = 18, the table t-value was 2.101. Thus, the calculated t-value is greater than the t-table value, i.e., t-calculated = 6.01 > t-table = 2.101. Based on the hypothesis testing criteria, if the calculated t-value is greater than the t-table value (t-calculated > t-table), then Ho is rejected, meaning HA is accepted. The conclusion of this study is that teaching styles can be an effective learning strategy to improve basic badminton skills in high school students.